PENGARUH KEBIJAKAN PEMERINTAH TERHADAP ANCAMAN PENGANGGURAN AKIBAT KENAIKAN INFLASI DI KOTA BANTEN PERIODE TRIWULAN II 2022 - Badra Maitri; Cindy Hartono; Fion Jennifer; Jesslyn; Jumi Liana; Hery Haryanto (ADAI Kepri, 2022)
The increase in inflation in Banten Province poses a threat to unemployment and government policies are needed to overcome this. The purpose of this study was to determine the root of the problem of high inflation and the influence of threats on unemployment, how fast the development of inflation in Quarter II on unemployment in Banten Province. The analysis was carried out using secondary data and a quantitative method approach based on numbers and nominals. The high unemployment rate in the second Quarter of Banten Province was due to the strategic nature of the migrant population moving to find work in Banten Province.